Analisis Pengaruh Variasi Kulit Ari Dan Model Hopper Terhadap Waktu Produksi Serta Tingkat Kehalusan Hasil Penggilingan - Farid Aziz Hardinansya; Arya Mahendra Sakti; Ferly Isnomo Abdi; Diah Wulandari (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This research is motivated by the ineffectiveness of stone model grinding machine in processing light, fibrous, and thin grain husk, so that a disc mill type FFC-15 grinding machine based on friction mechanism between discs was developed. The main objective is to analyze the effect of variations in husk type (mung bean, soybean, peanut) and hopper model (cylindrical, pentagonal, pyramidal) on production time, actual grinding capacity, level of fineness of the grinded results, and the extent to which differences in the physical characteristics of the husk affect the material flow rate in various hopper models with a test mass of 1 kg and a 1 mm sieve to understand the mechanism of non-homogeneous material flow in the grinding system. The experimental method involves testing the combination of the three types of husk and hopper, repeated three times, measuring production time, capacity (kg/hour), and percentage passing through a 1 mm sieve. The results showed an actual capacity of 2.70–4.71 kg/hour, where the pyramid hopper excelled with the shortest time, a maximum capacity of 4.71 kg/hour, and a fineness of 94.40% for mung bean hulls, while soybean hulls were the lowest due to unstable flow. The pyramid hopper proved to be the most effective in improving the hull grinding performance of grains.